Longitudinal association of movement behaviour and motor competence in childhood: A structural equation model, compositional, and isotemporal substitution analysis. Issue 8 (August 2022) - Estevan, Isaac; Clark, Cain; Molina-García, Javier; Menescardi, Cristina; Barton, Victoria; Queralt, Ana
Abstract: Objectives: The aim of this study was to analyse the association between physical activity and motor competence in primary school children using traditional and compositional data analysis approaches over time (time 1 and time 2). Design: A longitudinal observational design was used to study 124 typically developed children (45.2% girls), 5–10 years old at baseline. Methods: Children's objectively measured physical activity and sedentary behaviour, actual and perceived motor competence were assessed at two time points, one year apart. Longitudinal association of movement behaviors with actual and perceived motor competence, in locomotion, ball skills and overall motor competence was explored using structural equation models, compositional analysis, and isotemporal substitution. Results: When adjusted for sex, age, and body mass index, structural equation models and the composition consistently predicted actual and perceived motor competence at time 1 and time 2 ( p  < 0.01). Reallocation of 10 min from sedentary to light, or to moderate-to-vigorous physical activity, was associated with changes in actual motor competence, which was consistent from time 1 to time 2. Additionally, regarding self-perception, in time 1, isotemporal substitution of sedentary to light physical activity was the only reallocation associated with increases in perceived motor competence. In time 2, however, such positive associations were only found when reallocating time from sedentary or light to moderate-to-vigorous physical activity. Conclusions: Achieving adequate levels of moderate-to-vigorous physical activity, at the expense of sedentary and light physical activity, is associated with increases of actual and perceived motor competence over time.